PENGARUH STRATEGI WORKING BACKWARD DALAM PEMECAHAN MASALAH MATEMATIKA TERHADAP KEMAMPUAN PENALARAN SISWA SMP NEGERI KOTA JAMBI - Sufri, Sufri; Idrus, Ali (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2015)
Material mathematics and mathematical reasoning are two things that can not be separated, the material is understood through reasoning and mathematical reasoning to understand and learn the material drilled through mathematics. Working Backward strategy is a strategy that is closely associated with logical reasoning ability and verification. Working Backward strategy, students are required to analyze each step by using reasoning. This study used a quasi-experimental methods. This study aims to determine whether there are differences in the effect of the use of the Working Backward strategy in solving math problems on mathematical reasoning abilities of students. The experiment was conducted in Jambi City Junior High School. The population are 375 students, while the studied sample totaled 68 students consisting of 34 students in grade experiments and 34 students the control class. Sampling was done by using simple random sampling technique in class VII. Instruments in this study was a test in the form of mathematical reasoning abilities test description. The results showed that the average value of the experimental class of 74.92 and an average grade of 67.65 control. These results suggest that there are differences average value of the experimental class with the control class. So it can be concluded that the use of the Working Backward strategy in solving mathematical problems affect the ability of mathematical reasoning seventh grade students of SMP Negeri 11 Jambi. Keyword: Working Backward Strategy, Problem Solving, Reasoning Ability Mathematics